Twenty million angry men: the case for including convicted felons in our jury system - Binnall, James Michael (University of California Press, 2021)
Framing the issue -- Rotten to the core -- Honor among thieves -- Sequestering the convicted : part I -- Sequestering the convicted : part II -- Criminal desistance summonsed -- A Community change agent -- A Healthy ambivalence.